NOMINEE SHAREHOLDER POSITION IN INDONESIAN POSITIVE LAW - Christiari Gratiani Gamaitarak; Elvi Chaerani; Borgias Punto Billyarta (Universitas Labuhanbatu, 2024)
Economic development in Indonesia which is experiencing growth with the presence of integrating foreign capital in the business sector, makes foreign investors who wants to carry out business activities in Indonesia wants overall ownership or control of the business being carried out. These restrictions are regulated in Law Number 25 of 2007 concerning Investment, Law Number 40 of 2007 concerning Limited Liability Companies, and Burgelijk Wetboek (BW). The way to overcome these difficulties, foreign parties usually borrow names (nominee) in share ownership (nominee shareholder) by entering into a nominee arrangement. In this paper, we will discuss about the concept of the nominee shareholder and the position of the nominee shareholder according to Indonesian positive law.Keywords: nominee, nominee shereholder, nominee arrangement